2013
DOI: 10.5194/hess-17-3499-2013
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous estimation of model state variables and observation and forecast biases using a two-stage hybrid Kalman filter

Abstract: Abstract. In this paper, we present a two-stage hybrid Kalman filter to estimate both observation and forecast bias in hydrologic models, in addition to state variables. The biases are estimated using the discrete Kalman filter, and the state variables using the ensemble Kalman filter. A key issue in this multi-component assimilation scheme is the exact partitioning of the difference between observation and forecasts into state, forecast bias and observation bias updates. Here, the error covariances of the for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
(55 reference statements)
0
33
0
Order By: Relevance
“…Furthermore, recent studies have shown the more optimal correction of biases when applied to soil moisture anomaly observations (Albergel et al, 2012) and when applied over multi-temporal scales (Su & Ryu, 2015). Alternatively, bias correction could also be implemented online through estimation within a data assimilation scheme (De Lannoy et al, 2007;Pauwels, De Lannoy, Hendricks Franssen, & Vereecken, 2013). A thorough analysis of more comprehensive bias correction methods, including anomaly corrections and multi-scale analysis in a real data assimilation experiment could be an important subject for future research.…”
Section: Bias Removalmentioning
confidence: 97%
“…Furthermore, recent studies have shown the more optimal correction of biases when applied to soil moisture anomaly observations (Albergel et al, 2012) and when applied over multi-temporal scales (Su & Ryu, 2015). Alternatively, bias correction could also be implemented online through estimation within a data assimilation scheme (De Lannoy et al, 2007;Pauwels, De Lannoy, Hendricks Franssen, & Vereecken, 2013). A thorough analysis of more comprehensive bias correction methods, including anomaly corrections and multi-scale analysis in a real data assimilation experiment could be an important subject for future research.…”
Section: Bias Removalmentioning
confidence: 97%
“…In our SARbased WLOs, no significant bias between the SAR-derived and gauge levels could be detected (Mason et al, 2012b). For alternative processing chains, if WLO bias was found significant, and observation bias-aware DA scheme could potentially deal with this problem (e.g., Dee, 2005;Pauwels et al, 2013). …”
Section: Observation Quality Controlmentioning
confidence: 97%
“…The bias-blind state update innovations (i.e., the O 2 F residuals) are used to measure the forecast bias for the bias update, based on the assumption that the observations are unbiased, and persistence is used to predict the forecast bias. Pauwels et al (2013) recently extended the theory of the two-stage forecast bias and state estimation filter to simultaneously estimate separate observation and forecast biases. In their approach, demonstrated with synthetic experiments, the bias-blind state update innovation measures the observation bias plus the forecast bias, which is partitioned into the separate bias terms by calibration.…”
Section: Introductionmentioning
confidence: 99%